2012
DOI: 10.33549/physiolres.932344
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Stiffness in Primary Aldosteronism

Abstract: Aldosterone overproduction increases arterial wall stiffness by accumulation of different types of collagen fibres and growth factors. Our previous studies showed that central (aortic) arterial stiffness is increased in primary aldosteronism (PA) independently of concomitant hypertension and that these changes might be reversible after successful adrenalectomy. There is limited data available on the potential impact of mineralocorticoid overproduction on the deterioration of peripheral arterial stiffness. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
1
14
0
2
Order By: Relevance
“…baPWV evaluated muscular peripheral arteries and haPWV evaluated the combination of muscular peripheral arteries and elastic central arteries. In a previous study, PA pateints had both higher central and peripheral PWV than EH patients 28 . In the presented study, we found both baPWV and haPWV got improvement after adrenalectomy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…baPWV evaluated muscular peripheral arteries and haPWV evaluated the combination of muscular peripheral arteries and elastic central arteries. In a previous study, PA pateints had both higher central and peripheral PWV than EH patients 28 . In the presented study, we found both baPWV and haPWV got improvement after adrenalectomy.…”
Section: Discussionmentioning
confidence: 71%
“…PA patients have increases in both central-elastic and peripheral-muscular arterial stiffness 28 . Besides, PA patients have a thicker carotid intima-media layer, which may be due to carotid wall fibrosis 13 , and this can also be reversed after adrenalectomy in APA patients 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Pulse wave velocity (PWV) is regarded to be a reliable marker of arterial stiffness. Several studies showed increased PWV values as compared to EH patients and this difference was independent from BP levels on office and ABPM [53,54]. It is of interest that, in contrast to surgical treatment, medical treatment with spironolactone had no effect on aortic stiffness indices, including PWV.…”
Section: Vessels ▼mentioning
confidence: 97%
“…Nongenetic forms of HA are often treated surgically but chronic oral mineralocorticoid receptor (MR) antagonism, generally with spironolactone, has also been used to lower BP . It is believed that the end‐organ damage profile in patients with HA is more severe than essential hypertension, including increased prevalence of cerebral hemorrhage, myocardial infarction, left ventricular hypertrophy, cardiac fibrosis, increased arterial stiffness, microalbuminuria, and microcirculatory wall‐to‐lumen ratio . Attribution of HA‐associated target organ damage, however, is universally confounded by the effects of aging as well as the duration and degree of BP elevation (BP burden) .…”
Section: Introductionmentioning
confidence: 99%